Unlocking multimodality: E-scooters as first/last mile connectors and multimodal hub exploration in Doha - Ioannis Tsouros; Amalia Polydoropoulou; Athena Tsirimpa; Ioannis Karakikes; Shahram Tahmasseby; Anas Mohammed; Wael Alhajyaseen (Journal of Cycling and Micromobility Research, 2025)
Overcoming Doha's ''first/last-mile'' gap is critical if its new metro is to win riders in a car-oriented, hot-climate city. We therefore combined over 44,000 anonymised e-scooter GPS traces collected between December 2020 and August 2021 with hourly metro-gate counts and network-based walksheds around every station. Descriptive statistics, correlation tests and travel behaviour-centred user segmentation revealed how the two modes interact in space and time. Fifty-seven per cent of scooter trips began or ended within a short walk of a metro entrance, indicating significant spatial proximity between micromobility usage and transit infrastructure. Five distinct rider groups emerged: ''frequent commuters'' concentrate at central business-district stations, while ''infrequent weekend riders'' cluster at leisure destinations. Temporal analysis revealed strong integration potential across diverse station types: 8 out of 10 stations demonstrated temporal alignment between scooter activity and metro ridership, including business districts, cultural destinations, and residential areas. This alignment typically followed a logical pattern with ridership peaks, followed by scooter activity peaks consistent with multimodal trip-making. Only stations with minimal scooter activity showed patterns inconsistent with transit connectivity. These findings demonstrate that successful multimodal integration extends beyond business districts to include diverse urban contexts when supported by appropriate infrastructure. The Doha case shows that even in extreme heat climates, spatiotemporal analysis can guide effective micromobility policies that enhance both transit connectivity and broader urban accessibility.